Hydroethanolic Extracts of the Aristotelia Chilensis (Maqui) Berry Reduces Cellular Viability and Invasiveness in the Endometrial Cancer Cell Line Ishikawa - Cardenas-Sankan, G; Orihuela-Diaz, P; Elgueta-Bravo, E; Mena-Silva, J (SAGE Publications Inc., 2021)
Cancer of the reproductive tract includes diseases with higher prevalence in the female population. This investigation examined whether an anthocyanin-enriched extract of Aristotelia chilensis, commonly known as “maqui,” could affect some hallmarks of endometrial cancer. Cultures of the human endometrial cancer cell line Ishikawa were treated with a hydroethanolic maqui extract at 1, 3, 10, 30, 100, 300, or 1000 µg/mL to determine the effect on cell viability by MTT assay. Then, we used the 50% Effective Concentration (EC50) to evaluate whether the effect of the maqui extract is mediated via an arrest of the cell cycle or induction of apoptosis using flow cytometry or Annexin V-FITC assays, respectively. The effects of sublethal doses of the maqui extract on migration and invasiveness of Ishikawa cells were also evaluated by the wound healing and Boyden Chamber assay, respectively. Our results show that the hydroethanolic maqui extract inhibits the cell viability with an EC50 of 472.3 µg/mL via increased apoptosis, and that reduces the invasive capacity but not migration of Ishikawa cells. These findings suggest that the hydroethanolic maqui extract has antineoplastic properties for endometrial cancer and merits further studies to corroborate its efficiency as anticancer therapy in reproductive organs. © The Author(s) 2021.